Catholic Modernity and the Italian Constitution. Issue 1 (25th April 2016) - Thomassen, Bjørn; Forlenza, Rosario
Abstract : This article analyzes the Catholic contribution to the Italian republican and democratic Constitution of 1948. It focuses on the specific way – inspired by Catholic social philosophy – in which the Italian citizen became symbolically coded as a 'person' and not as an 'individual'. The Catholic project for the new Constitution had a considerable impact on modern Italian culture and politics and on the building of a modern mass democracy and welfare state. During the crucial historical juncture that followed the collapse of Fascism, Catholic politicians and intellectuals sought to interpret and give direction to the idea of political modernity, producing a positive encounter between Catholicism, democracy, and freedom. At the theoretical level, the argument is embedded within a larger aim to recognize attempts within Catholic philosophy and political thought to articulate a trajectory that moved away from the Enlightenment model, trying instead to articulate a Catholic, post-liberal and 'spiritual' political modernity.